Kresna Service Innovation (Responsive and Synergic Communication Between Apparatus and the Community) as a Government Communication Method in Kanigaran Village, Probolinggo City - Suprianto Suprianto; Andhi Nur Rahmadi; Farhan Fadillah Danuarta (The Future of Education Journal, 2026)
This study aims to examine KRESNA (Responsive and Synergistic Communication between Officials and the Community), a communication innovation implemented as a governmental communication tool in Kanigaran Subdistrict, Probolinggo City, given that communication between subdistrict officials and the community often remains formalistic and unresponsive, potentially creating information gaps and low public participation. The study employs a qualitative method with a descriptive approach to gain an in-depth understanding of the implementation of the KRESNA Forum based on the perspectives of subdistrict officials, the head of the neighborhood association (RW), and the subdistrict head (Lurah). The findings show that KRESNA functions effectively through four main aspects: the clarity of information delivered in detail through two-way communication, openness in conveying service procedures, officials' empathetic attitude in responding to community aspirations, and officials' ability to adapt messages to the community's diverse social and cultural backgrounds. This success is supported by harmonious cooperation among the subdistrict government, RW/RT leaders, and the community, as well as the continuously developed competence of subdistrict officials, although internal barriers such as limited facilities and heavy workloads, and external barriers such as uneven community participation, were still found. The study concludes that KRESNA represents a concrete form of responsive and participatory governmental communication, though strengthening outreach and supporting facilities is still needed to optimize its effectiveness.